Marius’ ‘grammar of assent’: Pater’s Dialogue with Newman - John Coates (Cahiers Victoriens et Edouardiens)
It is generally acknowledged that Newman’s influence was a significant factor in Pater’s rapprochement with Christianity in the 1880s. Drawn to Newman’s personality, Pater also found his intellectual approach congenial. Newman’s concepts of the organic developement of doctrine and of the ‘illative sense’, an innate human faculty which perceives when the convergence of probabilities amounts to truth, particularly appealed to him. However, the fact that Pater left his essay on ‘The Writings of Cardinal Newman’ unfinished is suggestive. As well as admiration for Newman, Pater had some reservations. In Marius the Epicurean, contemporary with the unfinished essay, he explores several points in which he differed from a writer he valued. The novel portrays a mind drawn to Christianity by a convergence of evidence such as Newman had envisaged but without the feeling of sin, pollution and retribution Newman considered universal. In a dialogic relation to Newman, and by examining the moral value of aesthetic experience, of isolated introspection and sublimated erotic instincts, Pater creates his own ‘grammar of assent’.